Short‐Duration High Frequency MegaHertz‐Order Nanomechanostimulation Drives Early and Persistent Osteogenic Differentiation in Mesenchymal Stem Cells (Small 8/2022). Issue 8 (24th February 2022) - Ambattu, Lizebona August; Gelmi, Amy; Yeo, Leslie Y.
Abstract : Osteogenic Differentiation In article number 2106823, Lizebona August Ambattu, Amy Gelmi, and Leslie Y. Yeo, expose mesenchymal stem cells to minutes of high frequency (10 MHz) mechanostimulation daily in the form of surface reflected bulk waves generated on a piezoelectric substrate, leading to their early but long‐term differentiation into osteoblasts.